Distribuição geográfica de Pyriglena spp. (AVES: THAMNOPHILIDAE) : avaliando o efeito de clima, interação biótica e complexidade do habitat - Santos, Caroline Silva dos (2018)
Models of potential distribution are important tools for studying biogeography and species conservation, helping to understand patterns of spatial distribution of organisms. However, for models to better represent the environmental conditions for species, they require environmental variables with relevant biological meaning, such as biotic interactions and habitat structure, beyond the commonly used climatic variables. In this regard, in this study, we aim to investigate the influence of four sets of predictors, including climatic variables, biotic interaction and habitat structure on the geographical distribution of birds of the genus Pyriglena. These birds inhabit forest environments, in the sub-forest stratum, and are included in the trophic guild of army ants followers. In addition to the bioclimatic layers, forest complexity layer was generated from two attributes combined (forest cover and canopy height) and an suitability models layer of army ants were used to generate the bird models. Models were developed using the Maxent algorithm and its performance measured through the TSS and AUC metrics. Models of birds of the genus Pyriglena indicate a greater influence of the macroclimate. Forest complexity was also an important predictor, with these birds occurring in areas that are under pressure due to the processes of habitat loss and fragmentation, and with their habitat requirements pointing to areas with mature forest and complex matrix. The biotic interaction layer had a low contribution in the models, inclusively worsening their performance, except for P. leuconota, which can be considered more specialized in the trophic guild of ant following. This study contemplates potentially suitable areas for large-scale spatial distribution of birds of the genus Pyriglena. This information can support conservation strategies for P. pernambucensis and P. atra, which are threatened with extinction.